Estructuras y objetos para interpretar la organización sociopolítica estatal y local en tell el-Ghaba (Sinaí Norte) entre los siglos x y vii a.C. - Calomino , Eva Amanda (Antiguo Oriente, 2025)
In this work, an approach to the sociopolitical organization of the Eastern Delta is proposed, focusing on the period between the mid-Third Intermediate Period and the Early Saite Period and on the study on certain objects and structures from the urban settlement of Tell el-Ghaba. This approach presents two main lines of inquiry: the first aims to understand the evidence that reflects state decisions concerning a site located on the ancient eastern Egyptian frontier; the second focuses on local issues, primarily related to domestic, administrative, and workshop contexts. Without a doubt, the Egyptian Delta has emerged in recent decades as a unique and paradigmatic area for studying both lines of research, primarily due to the types of constructions that have been erected and preserved, either in good condition or partially. To address these topics, this paper synthesizes aspects of the social, political, economic, and religious structure, organization, and characteristics, based on the study and compilation of excavated architectural structures and small finds with specific morphologies and thematic compositions related to activities associated with the site’s contexts.